Are Disability Rates among People with Diabetes Increasing in Germany? A Decomposition Analysis of Temporal Change between 2004 and 2015. (March 2021) - Sperlich, Stefanie; Beller, Johannes; Epping, Jelena; Safieddine, Batoul; Tetzlaff, Juliane; Geyer, Siegfried
Objectives: We investigated changes in the prevalence of disabilities among individuals with type 2 diabetes and analyzed the contribution of comorbidities on this change.Methods: Data were drawn from the Survey of Health, Ageing, and Retirement in Europe (SHARE). We estimated predicted probabilities of impaired (instrumental) activities of daily living (IADL and ADL) by means of logistic regression. Multivariate decomposition was employed for analyzing the impact of comorbidities on changes in disability rates.Results: Among people with diabetes, ADL difficulties rose significantly from 11.3% (2004) to 19.1% (2015), while IADL difficulties increased among younger diabetics from 11.5% to 18.3%. Decomposition analysis revealed that the parallel increase in comorbidities contributed to the rise in disabilities.Discussion: We found disability rates among people with diabetes in Germany to be increasing over time, pointing toward a growing demand of tertiary prevention for these individuals to maintain functional health and quality of life.